Male reproductive adjustments to an introduced nest predator. (19th July 2021) - Gravolin, Isaac; Lehtonen, Topi K; Deal, Nicholas D S; Candolin, Ulrika; Wong, Bob B M
Abstract: Nest predation has a large impact on reproductive success in many taxa. Defending offspring from would-be predators can also be energetically and physiologically costly for parents. Thus, to maximize their reproductive payoffs, individuals should adjust their reproductive behaviors in relation to the presence of nest predators. However, effects of nest predator presence on parental behaviors across multiple reproductive contexts remain poorly understood, particularly in non-avian taxa. We ran a series of experiments to test how the presence of an egg predator, the invasive rockpool shrimp, Palaemon elegans, influences male reproductive decisions and egg survival in a species of fish with exclusive paternal care, the three-spined stickleback, Gasterosteus aculeatus . We found that, in the presence of shrimp, male sticklebacks were less likely to build a nest, invested less in territory defense against an intruder, and tended to fan eggs in their nest less and in shorter bouts, but did not alter their investment in courtship behavior. The predator's presence also did not affect egg survival rates, suggesting that males effectively defended their brood from the shrimp. These results show that reproducing individuals can be highly responsive to the presence of nest predators and adjust their behavioral decisions accordingly across a suite of reproductive contexts. Abstract : Stickleback fish adjusted their reproductive behaviors to predator presence across a suite of contexts, from nest building to territory defense and parental care. We tested for responsiveness in such reproductive decisions because predators that pose a threat to young can directly impact the reproductive success of parents. This was done by running a series of experiments that tested the influence of the presence of an invasive egg predator, the rockpool shrimp, on reproducing stickleback males.